Riel's defence : perspectives on his speeches - Hansen, Hans V., 1948- (McGill-Queen's University Press, 2014)
In 1885, Louis Riel was charged with high treason, found guilty, and consequently executed for his role in Saskatchewan's North-West Rebellion. During his trial, the Metis leader gave two speeches, passionately defending the interests of the Metis in western Canada as well as his own life.